Endoscopic Extraction of CBD Stone: single centre experience in tertiary care centre
Background and Aims: Introduction: Endoscopic Retrograde Cholangiopancreatography(ERCP) has become the first line treatment for patients with common bile duct (CBD) stones. This technique may fail, however, due to presence of a large stone, multiple stones, periampullary diverticula or CBD stricture. The aim of this study was to evaluate the success of CBD cannulation, Endoscopic Sphincterotomy(EST) and CBD clearance in initial attempt, identify the failures of stone extraction and assess the post-ERCP complications. Methods: A prospective study was carried out over the period of January 2019 to January 2020 on 100 consecutive patients with CBD stones. ERCP was done and the stone size and number recorded. EST was performed using a diathermy unit with a cutting current and stones were extracted using a Balloon catheter or a Dormia basket. Results: Of the 100 patients, 44 were male and 56 were female with mean age of 52